2018
DOI: 10.17265/1934-8975/2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thickness of Polymer Electrolyte Membrane on Temperature Distributions in Single Cell of Polymer Electrolyte Fuel Cell Operated at High Temperature

Abstract: This study is to understand the impact of operating condition, especially initial operation temperature (T ini ) which is set in high temperature range, on the temperature profile of the interface between PEM (polymer electrolyte membrane) and catalyst layer at the cathode (i.e., the reaction surface) in a single PEFC (polymer electrolyte fuel cell). A 1D multi-plate heat transfer model based on the temperature data of separator measured using thermograph in a power generation experiment was developed to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 37 publications
0
19
0
1
Order By: Relevance
“…A few researchers [4] [22] [23] have reported numerical simulation on temperature distribution in a single PEFC which is operated at a higher temperature than usual. However, only a few papers [4] [22] have investigated the tempera-ture distribution on the interface between PEM and electrode at the cathode, which is defined as the reaction surface in this study, excluding the research conducted by the authors [24] [25] [26] [27]. The previous studies [24] [25] [26] [27] have confirmed the thickness effect of not only PEM but also GDL on the distribution of temperature at reaction surface (T react ) in a single PEFC at a higher temperature, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few researchers [4] [22] [23] have reported numerical simulation on temperature distribution in a single PEFC which is operated at a higher temperature than usual. However, only a few papers [4] [22] have investigated the tempera-ture distribution on the interface between PEM and electrode at the cathode, which is defined as the reaction surface in this study, excluding the research conducted by the authors [24] [25] [26] [27]. The previous studies [24] [25] [26] [27] have confirmed the thickness effect of not only PEM but also GDL on the distribution of temperature at reaction surface (T react ) in a single PEFC at a higher temperature, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few papers [4] [22] have investigated the tempera-ture distribution on the interface between PEM and electrode at the cathode, which is defined as the reaction surface in this study, excluding the research conducted by the authors [24] [25] [26] [27]. The previous studies [24] [25] [26] [27] have confirmed the thickness effect of not only PEM but also GDL on the distribution of temperature at reaction surface (T react ) in a single PEFC at a higher temperature, i.e. 90˚C or 100˚C by the heat transfer model using the experimental temperature distribution data gotten by means of thermograph.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…トスポットが生成すると電解質膜(PEM)の熱分解や,熱応力起因の破損が生じる ことから, 高温で運転する際にはこれまで以上に温度制御に配慮が必要となる. 200℃程度までの高温運転に関する PEFC の各種特性について報告例 (Chen and Su, 2018;Devrim et al, 2018;Kannan et al, 2018;Nalbant et al, 2018; はいくつかあるが,それらの多くが新材料の開発 (Devrim et al, 2018;や 電流密度や電圧変化のような発電特性評価 (Chen and Su, 2018;Nalbant et al, 2018;もしくは 耐久性評価 (Kannan et al, 2018;に関する報告であり,PEFC 単セル内部の温度分布特性につ いて評価した研究は少ない Lee et al, 2017;) .さらに,カソード還元 反応に重要な役割を担う PEM とカソード触媒層の界面(本論文では反応面と定義する)の温度分布について評 価した研究は,著者らの過去の取り組み Nishimura et al, 2018) Table 1 Specification of PEFC components referred from the manufacture catalog and previous studies (Nishimura et al, 2018;Cooper et al, 2017;Penga et al, 2016;Nishimura et al, 2012;Kang and Ju, 2009). conductivity is promoted by humidification of PEM and the thermal conductivity of GDL is promoted by penetration of MPL into GDL.…”
unclassified
“…Operating conditions of power generation for temperature measurement by thermograph. Area display of in-plane temperature distribution measured by thermograph Nishimura et al, 2018). …”
mentioning
confidence: 99%